Compounds from diverse natural origin against triple‐negative breast cancer: A comprehensive review. (15th November 2022) - Thilagavathi, Ramasamy; Priyankha, Sridhar; Kannan, Manivel; Prakash, Muthuramalingam; Selvam, Chelliah
Abstract: Triple‐negative breast cancer (TNBC) is caused due to the lack of estrogen receptors (ER), progesterone receptors (PR), and human epidermal growth factor 2 (HER2) expression. Triple‐negative breast cancer is the most aggressive heterogeneous disease that is capable of producing different clones and mutations. Tumorigenesis in TNBC is caused due to the mutation or overexpression of tumor suppressor genes. It is also associated with mutations in the BRCA gene which is linked to hereditary breast cancer. In addition, PARP proteins and checkpoint proteins also play a crucial function in causing TNBC. Many cell signaling pathways are dysregulated in TNBC. Even though chemotherapy and immunotherapy are good options for TNBC treatment, the response rates are still low in general. Many phytochemicals that are derived from natural compounds have shown very good inhibitions for TNBC. Natural compounds have the great advantage of being less toxic, having lesser side effects, and being easily available. The secondary metabolites such as alkaloids, terpenoids, steroids, and flavonoids in natural products make them promising inhibitors of TNBC. Their compositions also offer vital insights into inhibitory action, which could lead to new cancer‐fighting strategies. This review can help in understanding how naturally occurring substances and medicinal herbs decrease specific tumors and pave the way for the development of novel and extremely efficient antitumor therapies. Abstract : In this review, we reported extensive information about diverse molecules from natural source with anticancer activity in TNBC. The secondary metabolites such as alkaloids, terpenoids, steroids, and flavonoids in the natural products make them promising inhibitors of TNBC.